Evaluation of the Effect of Nanoparticle Graphene Oxide on Flexural Strength of Glass Ionomer Cements - Farahnaz Sharafeddin; Hajar Farhadpour; Reza Hefzollah (International Journal of Dentistry)
Aim. Glass ionomer (GIC) is a widely used restorative material in dentistry, but it has relatively weak mechanical properties. In this research, the effect of graphene oxide (GO) on the flexural strength of GIC was investigated. Materials and Methods. In this experimental study, 60 GIC samples in 6 groups of 10 were prepared, including Group 1: control conventional glass ionomer (CGIC), Group 2: CGIC + 1% wt of GO, Group 3: CGIC + 2% wt of GO, Group 4: control resin-modified glass ionomer (RMGI), Group 5: RMGI + 1% wt of GO, and Group 6: RMGI + 2% wt of GO. The samples were kept for 24 hours. The flexural strength of the samples was measured by using a universal testing machine. Data were analyzed by two-way ANOVA and posthoc Tukey test. (P<0.05). Results. In the RMGI groups, the mean flexural strength value of the RMGI + 2% GO group was significantly higher than that of the RMGI control group (P=0.027). In the comparison of RMGI groups with their corresponding CGIC groups, the mean flexural strength values of all RMGI groups were significantly more than CGIC groups (P<0.001). RMGI + 1% GO was not significantly different from control RMGI and RMGI + 2% GO (P=0.802, P=0.395, respectively). There was no significant difference between CGIC groups. Conclusion. Adding 2% by weight of GO to RMGI increases the flexural strength of RMGI, which could be of great importance in clinical practice in order to reinforce the mechanical properties of this dental material. The flexural strength of RMGI is higher than that of CGIC.